Supraharmonic estimation by polyphase DFT filter bank. (June 2021) - Mendes, Thais M.; Ferreira, Danton D.; Silva, Leandro R.M.; Khosravy, Mahdi; Meyer, Jan; Duque, Carlos A.
Abstract: As a side effect caused by new technologies, supraharmonics attracted the attention of researchers in recent years. Mitigation and analysis of supraharmonics distortions are of great importance to guarantee the power quality (PQ) available in the power grids since such distortions can cause serious damage to the grid-connected equipment. However, there are few works in literature reporting techniques for supraharmonics analysis, and PQ equipment is rarely capable of performing measurements in the supraharmonic range. This work proposes a supraharmonic estimation system utilizing a digital filter bank through a multirate digital signal processing technique. The polyphase decomposition applied in the decimating filter bank enables the simplification of the system implementation. Both synthetic and real signals are used to evaluate the technique in analyzing supraharmonic distortions. The proposed method shows a good application prospect in accurately measuring supraharmonics and with a significant reduction in computational complexity compared with the method presented in the IEC 61000-4-30 standard.